Controle jurisdicional de políticas públicas à luz do princípio da separação dos poderes - Brasileiro, Karina Pinto (2017)
The present research aims to verify the possibility of public policy control by the judiciary, without harming the principle of separation of powers and the administrative discretion, since these play important role in achieving the social fundamental rights, by virtue of the supremacy and normative constitutional force erected in neo-constitutionalism times and Democratic and Social State of law. It is through public policies that effect resource social rights, which currently assume position of relief against the other in positivized Magna Carta. The realization of these rights entails not necessarily negative for human dignity, since this is one of the pillars on which supports public policies. Deny social rights to the man, either by default, by inefficiency, or even, by the allegation of lack of resources (reservation possible theory), is to deny the human being to his own existence. Under this tuning fork, the public power, imbued with the social anxieties and aimed at the public interest, must act always with the eventual goal of achieving fundamental social rights, by means of public policies. Not doing, the Judiciary rises as a counter-majoritarian power to ensure the effectiveness of these, not having that talk about undue interference of this power to control them, as it is the guardian of the Constitution and the person responsible for implementation of the Democratic and Social State of law, in the light of the premises established by the neo-constitutionalism. In this way, this work is classified as an explanatory research with qualitative methodological aspect, since it was necessary to merge the views of various authors, contrasting their views, until it reaches its denouement. In addition, as a method of the deductive approach, using the method of Exegetical interpretation, whose larger premise is the Federal Constitution and the fact less the doctrinal and jurisprudential lectures taking place of your reception, and finally, as technical procedure and technique of bibliographic documentation research indirectly, since the research was developed based on materials already prepared , various authors, principally of books, scientific articles, case law and legislations.